2022
DOI: 10.3390/pr10112397
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Application of Acoustic Emission in Coal—Analysis Based on CiteSpace Knowledge Network

Abstract: Based on CiteSpace software, this paper reviews and analyzes the application articles of acoustic emission in coal from 2010 to 2020. In this paper, CiteSpace software visualizes 453 articles collected in the Web of Science core database. The cooperation networks between different countries, institutions, and authors are used to determine the connection of knowledge in papers. The keyword co-occurrence, keyword co-occurrence time zone map, and keyword clustering are used to determine the hot topics in the fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The advantages of detection methods currently used in this field are analyzed. Zhao et al [43] systematically combed and analyzed the academic literature on the application of acoustic emission technology in coal published worldwide from 2010 to 2020 in-depth using the visual analysis software CiteSpace. The results show that the time domain parameters of AE, such as cycle count, energy, waveform, and signal intensity, have reached a mature level.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of detection methods currently used in this field are analyzed. Zhao et al [43] systematically combed and analyzed the academic literature on the application of acoustic emission technology in coal published worldwide from 2010 to 2020 in-depth using the visual analysis software CiteSpace. The results show that the time domain parameters of AE, such as cycle count, energy, waveform, and signal intensity, have reached a mature level.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the coupling effects of multiple fields in rock mechanics and the engineering application of mature research outcomes would be the key focus of future freeze–thaw rock mechanics research. Zhao [ 22 ] conducted analysis and organizational research on the acoustic emission of steeply inclined coal using bibliometric software. The research findings have mainly been applied in geological surveys, mineral resource extraction, nuclear waste storage, and other related areas.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in many research elds such as information science, medicine, and environmental science (Chen et al, 2012;Hou et al, 2018;Zhu and Hua, 2017). Chao et al reviewed heavy metal pollution in CFPPs using bibliometric studies and the results showed that the recent hotspots were harmful trace elements and speciation analysis (Chao et al, 2021). Although atmospheric mercury is the most frequent keyword in this knowledge eld, there is still a gap in the metrological analysis of the subcategory of mercury emissions from CFPPs.In this study, we utilized the bibliometric software CiteSpace and the date from the Web of Science (WOS) core collection to analyze the knowledge structure of mercury emissions from CFPPs from 2000 to 2022.…”
mentioning
confidence: 99%